2014
DOI: 10.3389/fnsys.2014.00006
|View full text |Cite
|
Sign up to set email alerts
|

Spike sorting for polytrodes: a divide and conquer approach

Abstract: In order to determine patterns of neural activity, spike signals recorded by extracellular electrodes have to be clustered (sorted) with the aim of ensuring that each cluster represents all the spikes generated by an individual neuron. Many methods for spike sorting have been proposed but few are easily applicable to recordings from polytrodes which may have 16 or more recording sites. As with tetrodes, these are spaced sufficiently closely that signals from single neurons will usually be recorded on several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 51 publications
0
67
0
Order By: Relevance
“…Although fully-automated spike sorting has been of interest for many years (Abeles and Goldstein, 1977), and despite prior efforts to automate sorting algorithms (Calabrese and Paninski, 2011; Carlson et al, 2014; Einevoll et al, 2012; Ekanadham et al, 2014; Franke et al, 2010; Franke et al, 2015; Kadir et al, 2014; Lewicki, 1998; Marre et al, 2012; Pillow et al, 2013; Quiroga et al, 2004; Rodriguez and Laio, 2014; Swindale and Spacek, 2014; Takekawa et al, 2012), the majority of laboratories still rely heavily on manual intervention. In this work, we set out to develop a fully automated spike sorting algorithm having error rates that are comparable to or lower than those of existing manual and semi-manual approaches, and with runtimes faster than acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…Although fully-automated spike sorting has been of interest for many years (Abeles and Goldstein, 1977), and despite prior efforts to automate sorting algorithms (Calabrese and Paninski, 2011; Carlson et al, 2014; Einevoll et al, 2012; Ekanadham et al, 2014; Franke et al, 2010; Franke et al, 2015; Kadir et al, 2014; Lewicki, 1998; Marre et al, 2012; Pillow et al, 2013; Quiroga et al, 2004; Rodriguez and Laio, 2014; Swindale and Spacek, 2014; Takekawa et al, 2012), the majority of laboratories still rely heavily on manual intervention. In this work, we set out to develop a fully automated spike sorting algorithm having error rates that are comparable to or lower than those of existing manual and semi-manual approaches, and with runtimes faster than acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, we combine several key ideas: Divide-and-conquer. The first step is to try to divide the dataset into smaller subsets before applying any expensive clustering algorithms (Swindale and Spacek (2014)). This "divide-and-conquer" approach is critical for both statistical and computational reasons.…”
Section: 7mentioning
confidence: 99%
“…This same study also found as many as 24 single units in a virtual tetrode in the relatively sparse visual cortex. More recently, software algorithms that utilize precise spatial information as part of the sorting logic show great promise for improving both speed and accuracy 30,[80][81][82] . Investigating the optimal microelectrode size and pitch for speed and accuracy in spike sorting is an important research area.…”
Section: Recording Brain Activity Brief Historymentioning
confidence: 99%
“…where I i is the current of one point source, Ļƒ is the conductivity of the extracellular space, and r i is the distance from the source to the electrode (a dipole assumption results in a more complex isopotential and an amplitude proportional to 1/r 2 , but arguably the ratio is neither a monopole or dipole [28][29][30][31] ). Given the close spacing of tetrodes, multiple spike signals can be used to triangulate and localize a specific cell in space 32 .…”
Section: Recording Brain Activity Brief Historymentioning
confidence: 99%
See 1 more Smart Citation